2011
DOI: 10.1007/s00421-011-2046-5
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of catecholamine-synthesizing enzymes in adrenal medulla and stellate ganglia by treadmill exercise of stressed rats

Abstract: The sympatho-adrenal system represents one of the main systems involved in the response to stressful events because its stress-induced activation results in an increased release of catecholamines. Exercise training acts as an important modulator of sympatho-adrenal system, adrenal medulla and stellate ganglia being two components of this system. This study aimed at investigating physical exercise-related changes in gene expression of catecholamine biosynthetic enzymes tyrosine hydroxylase (TH), dopamine-β-hydr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
5

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 38 publications
0
13
0
5
Order By: Relevance
“…Exercise training offers as an important modulator of sympathoadrenal system, adrenal medulla, and stellate ganglia being two components of this system. Gavrilovic et al (2011) investigated physical exercise-related changes in gene expression of catecholamine biosynthetic enzymes tyrosine hydroxylase, dopamine-b-hydroxylase, and phenylethanolamine N-methyltransferase in the adrenal medulla and stellate ganglia of chronically psychosocially stressed adult rats exposed daily to 20-min treadmill exercise for 12 weeks. They observed that treadmill exercise induced decreased gene transcription of catecholamine biosynthetic enzymes in stellate ganglia and an attenuation of cardiac NA production during stressful situations.…”
Section: Physical Exercise As Interventionmentioning
confidence: 99%
“…Exercise training offers as an important modulator of sympathoadrenal system, adrenal medulla, and stellate ganglia being two components of this system. Gavrilovic et al (2011) investigated physical exercise-related changes in gene expression of catecholamine biosynthetic enzymes tyrosine hydroxylase, dopamine-b-hydroxylase, and phenylethanolamine N-methyltransferase in the adrenal medulla and stellate ganglia of chronically psychosocially stressed adult rats exposed daily to 20-min treadmill exercise for 12 weeks. They observed that treadmill exercise induced decreased gene transcription of catecholamine biosynthetic enzymes in stellate ganglia and an attenuation of cardiac NA production during stressful situations.…”
Section: Physical Exercise As Interventionmentioning
confidence: 99%
“…This may indicate a lower rate of catecholamines synthesis by the adrenal glands after longterm spontaneous exercise. However, there is no evidence in the literature showing a significant training effect on adrenaline and noradrenaline resting values in animals (24,25) and human studies (40,44,52,62). There are several reports on the composition and content of amino acids in the blood of rodents undergoing forced exercise (35).…”
Section: General Metabolic Effects Of Exercise In Animals At Restmentioning
confidence: 99%
“…; Gavrilovic et al . ). Based on these results and those reported in the literature, we hypothesized that oestrogen not only regulates the expression of stellate ganglion NA‐related proteins, but also directly affects the NET uptake function of the left ventricle (Moldovanova et al .…”
Section: Discussionmentioning
confidence: 97%